Status of Performances Rituals: Dance in Sacrifice Ceremony of Chao Poh Sri Thep - Phuphraingam, Somsak (Journal of Human and Society, Sisaket Rajabhat University, 2022)
Status of Performances Rituals : Dance in Sacrifice Ceremony of Chao Poh Sri Thep, is a qualitative thesis, the objectives to study history, configuration of sacrifice ceremony of Chao Poh Sri Thep, type of music and dance at Sri Thep Noi Sub-district, Sri Thep District, Phetchabun Province. By using the historical process, invention dance, chart of music and dance, study from the documents and concerning thesis and storage data field by participant observation and interview then present an information as the Descriptive Analysis , found that : The sacrifice ceremony of Chao Poh Sri Thep was an important worship which it was happened from the faith and respect to Chao Poh Sri Thep of people in Sri Thep District a long heritage, which they believed that Chao Poh Sri Thep will protect the people to be peaceful and happy. Which the configuration of sacrifice ceremony were 1. Persons 2. Time / Place 3. Oblation 4. Equipment For the type of music dance found that, use 2 kinds of musical instrument as a drum and a brass gong for this show and with the 7 styles of dance were 1. Walk 2. Sod Soi Mala 3. Yuang Krai 4. Give 5. Pray 6. Yoong Fon Hang 7. Point. Which it was a worship should be conserved to remain in the society for long.